Study of the morphology of the low-latitude D region ionosphere using the method of tweeks observed at Buon Ma Thuot, Dak Lak - Tan*, Le Minh; Thu, Nguyen Ngoc; Ha, Tran Quoc; Tuyen, Nguyen Thi Thao (Vietnam Journal of Earth Sciences, 2016)
Tweek is the electromagnetic waves at Extremely Low Frequency (3 - 3000 Hz) and Very Low Frequency (3-30 kHz) bands, which originates from lightning discharges and propagates about thousands of kilometers in the Earth-Ionosphere waveguide. Recording the tweeks with a maximum up to eighth harmonics using the receiver installed at Tay Nguyen University (12.65oN, 108.02oE), Buon Ma Thuot, Dak Lak, during January - June 2013, we have studied the morphology of the low-latitude D region ionosphere in the nighttime. The occurrence of  tweeks with mode number m = 2 - 3 is more dominant. Tweeks with higher modes (m ≥ 4) appear less than other tweeks due to the higher attenuation of wave energy for higher modes reflected at the ionospheric D region. The results show that electron density varies from 25.1-189.4 cm-3, corresponding to the tweeks with m = 1-8 at the reflection height from 82.2-86.5 km. The reference height h’ and electron density gradient β are higher during summer seasons as compared to those during winter and equinox seasons. The mean values of h’ and β are 82.5 km and 0.53 km-1, respectively. The electron density using the tweek method is lower by about 11-38 % than those obtained using the IRI-2012 model.References Bremer, J. and Singer W., 1977. Diurnal, seasonal, and solar-cycle variations of electron densities in the ionospheric D and E region, J. Atmos. Terr. Phys., 39,  25-34. Budden, K. G., 1961. The Wave-Guide Mode Theory of Wave Propagation, Logos Press, London, pp. 325. Budden, K. G., 1962: The inﬂuence of the earth’s magnetic ﬁeld on radio propagation of wave-guide modes. Proceedings of the Royal Society A, 265, 538-553. Cannam, C., Landone C., and Sandler M., 2010. Sonic Visualiser: An Open Source Application for Viewing, Analysing, and Annotating Music Audio Files. Proceedings of the ACM Multimedia 2010 International Conference. Danilov, A. D., 1998. Solar activity effects in the ionospheric D region, Ann. Geophys., 16, 1527-1533. Davies, K., 1965. Ionospheric Radio Propagation, National Bureau of Standard Monogragh 80, Washington, pp. 487. Hargreaves, J. K., 1992. The Solar-Terrestrial Environment, Cambridge Univ. Press, pp. 420. Heaps, M. G., 1978. Parameterization of the cosmic ray ion-pair production rate above 18 km, Planet. Space Sci., 26, 513-517. Helliwell, R. A., 1965. Whistlers and Related Ionospheric Phenomena, Stanford University Press, USA, pp. 368 Inan, U. S., Cummer, S. A., and Marshall, R. A., 2010. A survey of ELF and VLF research on lightning-ionosphere interactions and causative discharges, J. Geophys. Res., 115, A00E36. Kumar, S., Deo A., and Ramachandran V., 2009: Nightime D-region equivalent electron density determined from tweek sferics observed in the South Pacific Region, Earth Planets Space, 61, 905-911. Kumar, S., Kishore A., and Ramachandran V., 2008. Higher  harmonic  tweek  sferics  observed  at  low  latitude:  estimation  of  VLF  reflection  heights  and  tweek propagation distance,  Ann. Geophys, 26, 1451-1459. Le Huy Minh, Tran Thi Lan, C. Amory -Mazaudier, R. Fleury, A. Bourdillon, J. Hu, Vu Tuan Hung, Nguyen Chien Thang, Le Truong Thanh, Nguyen Ha Thanh, 2016. Continuous GPS network in Vietnam and results of study on the total electron content in the Southeast Asian region, Vietnam Journal of  Earth Sci.,  38 (2), doi: 10.15625/0866-7187/38/2/8598. Maurya, A. K., Veenadhari, B., Singh, R., Kumar, S., et al., 2012. Nighttime D region electron density measurements from ELF-VLF tweek radio atmospherics recorded at low latitudes, J. Geophys. Res., 117. Ohya, H., Nishino M., Murayama Y., and Igarashi K., 2003. Equivalent electron density at reflection heights of tweek atmospherics in the low - middle latitude D-region ionosphere, Earth Planets Space, 55, 627-635. Ohya, H., Nishino, M., Murayama, Y., Igarashi, K., 1981. Effects of land and sea parameters on the dispersion of tweek atmospherics, J. Atmos. Terr. Phys. 43, 1271-1277. Ohya, H., Shiokawa K., and Miyoshi Y., 2008. Development of an automatic procedure to estimate the reflection height of tweek atmospherics, Earth Planets Space, 60, 837-843. Prasad, R., 1981. Effects of land and sea parameters on the dispersion of tweek atmospherics, J. Atmos. Terr. Phys., 43, 1271-1273, 1275-1277. Saini, S. and Gwal A. K., 2010. Study of variation in the lower ionospheric reflection height with polar day length at Antarctic station Maitri: Estimated with tweek atmospherics, J. Geophys. Res., 115, A05302. Shariff, K.K.M., Salut, M. M., Abdullah, M., and Graf, K. L. 2011. Investigation of the D-region ionosphere characteristics using tweek atmospherics at low latitudes.  Proceeding of the 2011 IEEE International Conference on Space Science and Communication, 12-13 July 2011, Penang, Malaysia. Shvets, A. V., and Hayakawa M., 1998. Polarization effects for tweek propagation. J. Atmos. Terr. Phys., 60, 461- 469. Tan, L. M., Thu, N. N., Ha, T. Q., 2014. Observation of the effects of solar flares on the NWC signal using the new VLF receiver at Tay Nguyen University, Sun & Geosphere, 8, 27-31. Wait, J. R. and Spies K. P., 1964. Characteristics of the Earth-ionosphere waveguide for VLF radio waves. NBS Tech. Not.,  pp.300. Wood, G. T., 2004. Geo-loaction of individual lightning discharges using impulsive VLF electromagnetic waveforms. Ph.D. Thesis, Stanford University. Yamashita, M., 1978. Propagation of tweek atmospherics. J. Atmos. Terr. Phys., 40, 151-153, 155-156. http://www.ultramsk.com/software/